EVALUASI PENERAPAN SISTEM INFORMASI AKUNTANSI PENDAPATAN ATAS PELAYANAN KESEHATAN PASIEN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) DI PT PETRO GRAHA MEDIKA GRESIK - Suparman, Petrus; Febriana, Eli (GEMA EKONOMI, 2018)
This study aims to identify and evaluate and evaluate the effectiveness of the application of revenue accounting information systems for health services of patients of Badan Penyelenggara Jaminan Sosial (BPJS) in PT Petro Graha Medika, whether in accordance with the elements of accounting information systems. This research use descriptive method that is method analyze data which data collected, compiled and analyzed so as to give solution about problem faced.The object of this research is the application of revenue accounting information system in PT Petro Graha Medika. The data used in this study is qualitative. The results of this study indicate that the application of accounting information system on income for health services of patients of Badan Penyelenggara Jaminan Sosial (BPJS) in PT Petro Graha Medika has been running well and quite effective. There are good procedures, complete documents. DOI : 10.5281/zenodo.3477659